2017
DOI: 10.1016/j.ajpath.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Mechanisms of Bladder Repair after Hyaluronan Instillation in Ketamine-Induced Ulcerative Cystitis in Animal Model

Abstract: Ketamine-induced ulcerative cystitis (KIC) initially damaged the bladder mucosa and induced contracted bladder thereafter. Hyaluronan (hyaluronic acid; HA) instillation to the bladder has been used to treat KIC. The present study investigated bladder injury by urothelial defect and HA degeneration and bladder repair by urothelium proliferation and differentiation. This work was based on the hypothesis that HA treatment altered the bladder urothelial layer and the expression of hyaluronan-metabolizing enzymes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 62 publications
6
45
0
Order By: Relevance
“…In severe cases of KIC, augmentation enterocystoplasty might be beneficial in relieving refractory KIC pain and urinary symptoms but with a high risk of perioperative morbidity and long‐term complications . Researchers have attempted to develop experimental therapeutic strategies to treat KIC in patients or in animal models, including intravesical instillation of hyaluronic acid for protecting the bladder mucosa and applications of botulinum toxin A for inhibiting bladder neurotransmission. Nevertheless, the pathogenesis of KIC is complex and may result from direct toxic effects, bladder barrier dysfunction, neurogenic inflammation, and autoimmune reactions .…”
Section: Introductionmentioning
confidence: 99%
“…In severe cases of KIC, augmentation enterocystoplasty might be beneficial in relieving refractory KIC pain and urinary symptoms but with a high risk of perioperative morbidity and long‐term complications . Researchers have attempted to develop experimental therapeutic strategies to treat KIC in patients or in animal models, including intravesical instillation of hyaluronic acid for protecting the bladder mucosa and applications of botulinum toxin A for inhibiting bladder neurotransmission. Nevertheless, the pathogenesis of KIC is complex and may result from direct toxic effects, bladder barrier dysfunction, neurogenic inflammation, and autoimmune reactions .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, glycosaminoglycan instillation can achieve relief of pain, frequency, and hematuria in patients without signs of fibrosis nor complications involving the upper urinary tract. This result is probably related to the restoration of urothelium barrier function, the enhanced mucosal regeneration and the decreased interstitial fibrosis 79 …”
Section: Evidencementioning
confidence: 88%
“…Previous studies using Sprague Dawley (SD) rats have demonstrated that TGF-β1 signaling (48) and EMT (9) are associated with ketamine-induced fibrosis. Furthermore, injection of human umbilical cord blood-derived mesenchymal stem cells or antifibrotic compounds, including N-acetylcysteine (49) and hyaluronic acid (50), in SD rat bladder tissue have been demonstrated to decrease fibrosis by inactivating TGF-β signaling. However, TGF-β-associated genes were unaltered in the present microarray analysis.…”
Section: Discussionmentioning
confidence: 99%